Synthesis and hydrogen storage property tuning of Zr(BH4)4·8NH3 via physical vapour deposition and composite formation. (11th October 2018) - Wu, D.F.; Ouyang, L.Z.; Huang, J.M.; Liu, J.W.; Wang, H.; Shao, H.; Zhu, M.
Abstract: Zr(BH4 )4 ·8NH3 is considered to be a promising solid state hydrogen-storage material, due to its high hydrogen capacity and low dehydrogenation temperature. However, the possible applications of Zr(BH4 )4 ·8NH3 have been greatly hampered by the complicated and less applicable synthesis process, which must be operated at relatively low temperature (<20 °C). Herein, we reported a simple and facile "heating-(ball milling) BM vial" method via physical vapour deposition to tackle this issue. By this technique, Zr(BH4 )4 ·8NH3 was successfully synthesized. Furthermore, composite formation by adding 10 wt% NaBH4 to the as-prepared Zr(BH4 )4 ·8NH3 was found to be able to lower down the dehydrogenation peak of Zr(BH4 )4 ·8NH3 from 130 to 75 °C and more excitingly, the possible emission of B2 H6 and NH3 from dehydrogenation of only Zr(BH4 )4 ·8NH3 was completely suppressed after addition of NaBH4 . This research presents a new hydrogen-storage system based on Zr(BH4 )4 ·8NH3 +NaBH4 composite and it also implies a new development methodology of future hydrogen storage materials. Highlights: A facile Zr(BH4 )4 ·8NH3 synthetic method, "heating-ball milling vial" was reported. Some other unstable metal borohydride ammoniates may be synthesized by this method. NaBH4 might play as a catalyst in the dehydrogenation of Zr(BH4 )4 ·8NH3 .